Highly reversible zinc metal anodes enabled by protonated melamine. Issue 12 (21st February 2022) - Huang, Cong; Zhao, Xin; Hao, Yisu; Yang, Yujie; Qian, Yang; Chang, Ge; Zhang, Yan; Tang, Qunli; Hu, Aiping; Liu, Zhixiao; Chen, Xiaohua
Abstract : This work reveals the protonation reaction of melamine (Mel) in ZnSO4 electrolyte. It is demonstrated that protonated Mel is capable of regulating the electrical double layer structure for suppressing the side reactions and dendrite formation. Abstract : Zinc anodes have been troubled with serious side reactions and uncontrollable dendrite growth, which is attributed to the unstable electrical double layer (EDL) structure. Herein, a nitrogen-based organic compound named melamine (Mel) is introduced for the first time into 2 M ZnSO4 solution for stabilizing the Zn anode. It is found that protonated Mel (MelH + ) is the predominant species in the ZnSO4 electrolyte instead of Mel itself. In the presence of MelH +, a stable EDL structure is obtained near the Zn anode surface, which inhibits side reactions between the electrolyte and the Zn anode. In addition, the positively charged MelH + can regulate the diffusion of Zn 2+ ions, thus inducing uniform Zn deposition. Consequently, the Mel/ZnSO4 electrolyte enables Zn|Zn symmetrical cells to exhibit an ultralong cycle life of 3000 hours and Zn|Cu half-cells to deliver a high average coulombic efficiency (CE) of 99.7% for 1200 cycles (1200 hours). Moreover, excellent performance is also demonstrated in Zn-ion hybrid supercapacitors (ZHSs) using activated carbon cloth as a cathode.